Understanding bacteria - Dowd, Marijo; Discovery channel (Singapore : International Publishers Direct, 1998)
This video tours on determine what is bacteria, discussion of its evolution, the impact it has had on man and the treatments for various bacteria.
Executive producer, Nancy LeBrun ; executive editor, Walter Cronkite
Narrator: Jane Curtin
Keywords: Bacteria; Microorganisms